IMPLEMENTATION OF ELECTRONIC LAND CERTIFICATES AS LEGAL LAND OWNERSHIP - Andriana Rachmah; Benny Djaja; Maman Sudirman (Transpublika Publisher, 2024)
With the issuance of Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 1 of 2021 concerning Electronic Certificates, this is a new breakthrough from the government to protect the public and provide legal certainty regarding ownership of land rights. Due to the frequent occurrence of various land disputes which will ultimately be detrimental to society, such as falsification of land certificates, the existence of multiple land certificates or overlapping land certificates and the rise of the land mafia. The problem formulation for this research is how to implement the implementation of electronic land certificates as legal land ownership? and what about legal protection and certainty after the implementation of electronic land certificates? In practice, Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 1 of 2021 concerning electronic certificates is relevant to be implemented today in line with the rapid development of science, technology and information. Legal certainty in the process of obtaining land rights is based on statutory rules and government regulations to prevent misuse of land rights, and can provide legal protection for land rights owners. This Ministerial Regulation aims to realize the modernization of land services in order to improve indicators of ease of doing business and public services to the community, thereby optimizing the use of information and communication technology by implementing electronic-based land services.